Upgrade Egyptian biogas to meet the natural gas network quality standard - Sameh Tawfik Abd Elfattah (Alexandria Engineering Journal, 2016)
Biogas is one of the promising renewable energy sources in Egypt. The objective of this research was to treat the raw biogas in order to clean it from acidic gases CO2 and H2S to meet the standard of the natural gas network. The acidic gases treating plant of the biogas were built up and numerically simulated using Aspen HYSYS 8.6 and a proper design of the plant was performed. The main purpose of the simulation is to determine the optimum working pressure, which can achieve the methane purity of the Egyptian biogas comparable to natural gas quality. The biogas treating process was accomplished inside Pressure Swing Absorber (PSA) where the feed sour gas enters the absorber at the CO2 contents of 0.25, H2S contents of 0.0004, a temperature of 30 °C, a pressure of 1.1 bars, a flow rate of 13 m3/h, Diethanolamine (DEA) concentration of 0.3 and 20 stages PSA with a tray diameter of 1.7 m. it is found that a PSA working pressure of 5 bars is required to obtain a biogas with methane purity of 95%.